2018
DOI: 10.4103/jisp.jisp_272_18
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of periodontally diseased molars in smokers using the Miller–McEntire Periodontal Prognostic Index

Abstract: Background:The purpose of this 2-year prospective survival analysis study is to determine a statistically validated periodontal prognostic score for diseased molars in smokers using the Miller-McEntire Periodontal Prognostic Index (MMPPI).Materials and Methods:Two hundred molars were evaluated from 25 patients who were smokers with moderate-to-severe chronic periodontitis. The factors evaluated included age, probing depth, mobility, furcation involvement, smoking, and molar type. A modified, 5 level, scoring c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 31 publications
3
22
1
Order By: Relevance
“…We then explored the independent risk factors for poor prognosis of patients with chronic periodontitis and found that the higher the periodontal pockets, the higher the loss of attachment; lower FGD5-AS1 and higher miR-130a levels were independent risk factors for their prognosis. In previous studies, age, bone height, and periodontal pocket were mentioned as prognostic factors of patients [ 23 , 24 ], while our study first found that FGD5-AS1 and miR-130a were also independent prognostic factors of chronic periodontitis. Hence, in the future, we can predict the prognosis of patients through the levels of two indicators, so as to implement the corresponding treatment plans.…”
Section: Discussionsupporting
confidence: 50%
“…We then explored the independent risk factors for poor prognosis of patients with chronic periodontitis and found that the higher the periodontal pockets, the higher the loss of attachment; lower FGD5-AS1 and higher miR-130a levels were independent risk factors for their prognosis. In previous studies, age, bone height, and periodontal pocket were mentioned as prognostic factors of patients [ 23 , 24 ], while our study first found that FGD5-AS1 and miR-130a were also independent prognostic factors of chronic periodontitis. Hence, in the future, we can predict the prognosis of patients through the levels of two indicators, so as to implement the corresponding treatment plans.…”
Section: Discussionsupporting
confidence: 50%
“…A subsection of the patients from this cohort has been reported. [ 6 7 ] All study procedures were conducted after approval from the institutional ethics committee and have been described earlier, and written informed consent was obtained from all the 129 patients. [ 6 7 ] The sample size was computed assuming an expected event rate of tooth loss of 0.12 teeth/year, as reported for a periodontal maintenance group earlier, a planned follow-up period of 5 years, alpha = 0.05, and beta = 0.8.…”
Section: Methodsmentioning
confidence: 99%
“…[ 6 7 ] All study procedures were conducted after approval from the institutional ethics committee and have been described earlier, and written informed consent was obtained from all the 129 patients. [ 6 7 ] The sample size was computed assuming an expected event rate of tooth loss of 0.12 teeth/year, as reported for a periodontal maintenance group earlier, a planned follow-up period of 5 years, alpha = 0.05, and beta = 0.8. [ 8 ] At the end of the follow-up period, all patients exited by remaining in the regular periodontal maintenance program at the postgraduate periodontics clinics.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations